Effectiveness of Jambi Forest Honey and Klanceng Honey in Inhibiting Escherichia coli and Klebsiella pneumonia ESBL - Ardy Prian Nirwana; Yusianti Silviani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Bacterial resistance to antibiotics is a global problem that occurs around the world, both in hospitals and in communities. Antibiotic resistance can affect therapeutic outcomes, therapeutic costs, the spread of disease, and length of illness. The purpose of this study is to find out the potential of Jambi forest honey and Klanceng Honey in inhibiting the growth of ESBL-producing Escherichia coli and Klebsiella pneumonia. This study used experimental laboratory using posttest with control approach, conducted at the STIKES Nasional Bacteriology laboratory. The results showed that Jambi forest honey and Klanceng honey had better potential to inhibit the growth of ESBL-producing Escherichia coli and Klebsiella pneumonia than cefotaxime and ceftriaxone, but less than ceftazidime. On the other hand, honey samples had weaker inhibition potential against positive control (ciprofloxacin for K pneumoniae and chloramphenicol for E coli).